The Influence of the Mother of the Mattress Song on the Profile of Pancasila Students in Grade 1 Students in Independent Curriculum Elementary Schools - Chalifalillah Chalifalillah; Mas Roro Wahyu Diah Lestari (Publikasi Indonesia, 2025)
Character education is an important aspect in elementary school learning, especially in forming the Pancasila Student Profile according to the Merdeka Curriculum. One innovative method that can be used is the use of children's songs as a learning medium. This study aims to analyze the effect of using the song